Empowering Bojonegoro Handicraft MSMEs through digital marketing and financial literacy assistance - Yossy Imam Candika; Riska Nur Rosyidiana; Gaby Silvy Fauziah (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2025)
The handicraft industry in Bojonegoro, East Java, holds significant potential through products such as Jonegoroan batik, batik painting, knitted products, and teakwood crafts. However, members of the Asosiasi Handicraft Jatim (AHJ) Bojonegoro still face critical challenges in digital marketing and financial management. Limited use of Google Business Profile and the absence of systematic bookkeeping have restricted market reach and weakened sustainability. To address this issue, a community service program was conducted with the aim of empowering local artisans through knowledge transfer and practical mentoring. The method was implemented in five stages: planning, implementation, evaluation, feedback, and sustainability. The implementation included two main sessions, namely digital marketing and financial literacy training, complemented by mentoring and practice. 30 MSMEs owners participate in the program, and pre- and post-tests revealed significant improvement in knowledge. Evaluation results showed positive responses, with participants expressing strong interest in the continuation of similar programs. This mentoring program contributed to enhancing partners’ capacity to expand market reach, improve business financial management practices, and strengthen the economic competitiveness of handicraft MSMEs in Bojonegoro in a sustainable manner.